Formulation and evaluation of oral disintegrating tablets of furosemide: Formulation of ODTs of Furosemide (World Journal of Current Medical and Pharmaceutical Research, 2021)
Orally disintegrating tablets of Furosemide were prepared, evaluated and the comparison of the action of different concentrations of disintegrants on disintegration and dissolution of the tablets were studied. Direct compression method was used to prepare the orally disintegrating tablets containing 20 mg of Furosemide. The formulation was conducted using different concentrations of crospovidone, croscarmellose and sodium starch glycolate as superdisintegrants and their interactions with Furosemide were also evaluated using FTIR.  FTIR studies using the drug and its mixtures with the excipients showed that the peaks correlate with one another which signify that there is no interaction between the drug molecule and the excipients used. The obtained results revealed that the disintegration time of ODTs were between 9 to 59 seconds. The percentage drug content of tablets in all the formulations was found between 91.51% to 106.69%, which complies with the limits established in pharmacopoeia. The in-vitro dissolution studies show maximum release of 89.47% in formulation F3 and minimum of 77.64% in formulation F12. Higher concentration of crospovidone and croscarmellose in formulations F3 and F6 showed better dissolution properties than SSG. So by varying the concentrations of superdisintegrants, oral disintegrating tablets can be formulated.